Pengaruh FoMO dan Influencer Marketing, terhadap Impulse Buying yang di Mediasi Oleh Self Control pada Produk Glad2glow - Anita Anita; Chalid Imran Musa; Muhammad Ilham Wardhana Haeruddin; Muhammad Ichwan Musa; Rahmat Riwayat Abadi (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2026)
This study aims to analyze the influence of Fear of Missing Out (FoMO) and Influencer Marketing on Impulse Buying with Self-Control as a mediating variable among Glad2Glow consumers. The research applies a quantitative approach with the Structural Equation Modeling (SEM) method using SmartPLS 4 software. The population in this study were students of the Faculty of Economics and Business, Universitas Negeri Makassar, with a sample of 150 respondents selected through purposive sampling. The results show that FoMO has a positive and significant effect on Self-Control, while Influencer Marketing has no significant effect on Self-Control. Furthermore, Self-Control has a positive and significant effect on Impulse Buying, although the direction differs from the theoretical expectation. Both FoMO and Influencer Marketing have a positive and significant direct influence on Impulse Buying. In addition, Self-Control partially mediates the effect of FoMO on Impulse Buying but does not significantly mediate the effect of Influencer Marketing. These findings indicate that emotional drives caused by FoMO and the persuasive influence of social media influencers remain dominant factors that encourage impulsive buying behavior among Glad2Glow consumers.